Modulation of the Formation Mechanism of Thermally Induced Gels Containing Whole Oyster-Soybean Isolate Proteins by Hydrophilic Colloids - Mengting CAI; Li LIU; Ruonan HUANG; Xuening SUN; Mingyong ZENG (Shipin gongye ke-ji)
This study aimed to utilize oyster resources more effectively and provide novel feasible methods for the production of oyster gel products. In this study, the gelation mechanism of whole oyster-soybean isolate protein composite gels was systematically analyzed. Moreover, the key factors of hydrophilic colloids that regulate thermally induced gel formation and their effects on the gel properties of thermally irreversible composite gels were determined. The rheological properties, gel strength, infrared spectroscopy, interaction force, and microstructure of whole oyster-soybean protein isolate composite gels prepared with different konjac glucan (KGM)/κ-carrageenan (κ-C) ratios (0:5, 2:3, 1:1, 3:2, 4:1, 5:0）and different amounts of Ca(OH)2 (0.4%, 0.6%, 0.8%, 0.9%, 1.0%) added were investigated. The results indicated that as the KGM/κ-C ratio and the amount of Ca(OH)2 increase, the gel properties of the composite gel were significantly improved, characterized by a higher gelation point and enhanced solid-like attributes. This improvement was primarily attributed to the strengthened intermolecular hydrogen bonding, which leaded to a more compact microstructure of the composite gel. The best performance under different conditions was observed when the gels were prepared with a KGM/κ-C ratio of 3:2 (m/m) and Ca(OH)2 addition of 0.8% (m/v).